Performance of the multidisciplinary health team in cases of sexual abuse in children and adolescents (Research, Society and Development, 2020)
Objective: to characterize the role of the multidisciplinary health team in the face of cases of sexual abuse in children and adolescents. Method: a descriptive, exploratory, cross-sectional study with a quantitative approach, carried out with 102 health professionals from Primary Care in a city in Minas Gerais. A semi-structured questionnaire was used as a data collection instrument. These were analyzed according to the simple descriptive analytical epidemiology. Results: prevalence of female professionals, between 18 and 30 years old, health workers, complete high school and length of service between 1-3 years. Only 28.4% treated victims of sexual abuse, whose prevalence was among adolescents aged 12-18 years. Of the sample, 85.2% reported knowing how to identify sexual abuse; 74.5% observe the behavior of children and adolescents during home visits; 60.7% communicate to the superior and 36.2% inform having a service flowchart, but it is not printed, as it varies according to the victim's need. It is observed that most professionals did not participate in courses or training in the continuing education service. Conclusion: most of the interviewed professionals answered that they knew clinical signs of sexual abuse and the conduct to be taken upon the confirmation of this fact. However, few have experience in caring for victims of sexual abuse and most responded that they had not participated in continuing education on sexual abuse.